2021
DOI: 10.3390/app11094292
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Convolutional-Neural-Network Architecture for Crop Classification

Abstract: Automatic crop identification and monitoring is a key element in enhancing food production processes as well as diminishing the related environmental impact. Although several efficient deep learning techniques have emerged in the field of multispectral imagery analysis, the crop classification problem still needs more accurate solutions. This work introduces a competitive methodology for crop classification from multispectral satellite imagery mainly using an enhanced 2D convolutional neural network (2D-CNN) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Studies applying an ANN for LULC classification found that when compared with other models, especially the ones based on decision trees, the ANN tends to present a lower performance , which can be associated with its limited number of hidden layers. The use of convolutional and recurrent neural networks (CNNs and RNNs, respectively) has been suggested to solve this ANN problem [69]. However, the computational cost can be high, mainly when the time series of high-resolution images are involved.…”
Section: Accuracy Assessment and Importance Of Variablesmentioning
confidence: 99%
“…Studies applying an ANN for LULC classification found that when compared with other models, especially the ones based on decision trees, the ANN tends to present a lower performance , which can be associated with its limited number of hidden layers. The use of convolutional and recurrent neural networks (CNNs and RNNs, respectively) has been suggested to solve this ANN problem [69]. However, the computational cost can be high, mainly when the time series of high-resolution images are involved.…”
Section: Accuracy Assessment and Importance Of Variablesmentioning
confidence: 99%
“…Rustowicz et al [38]mentioned that applying 2DCNN to crops has a considerable level. Moreno-Revelo et al [39] used tens of plant types for classification with good accuracy. Toraman [40] used it for predicting epileptic attacks and identifying ongoing seizures.…”
Section: D-cnnmentioning
confidence: 99%
“…This enables efficient and real-time crop identification [10][11][12][13][14][15][16][17][18][19][20]. Among them, machine learning (ML) and deep learning (DL) [21][22][23][24][25][26][27][28] methods have been proven effective in extracting agricultural information from remote sensing data. These methods (ML and DL) utilize feature learning to achieve target classification, leading to improved information extraction results.…”
Section: Introductionmentioning
confidence: 99%